Carbothermal synthesis of micron‐sized, uniform, spherical silicon carbide (SiC) particles. Issue 22 (30th September 2021) - Feller, Tanja; Rosenfeldt, Sabine; Retsch, Markus
Abstract: Silicon carbide (SiC) particles are exciting structures because of their hardness, chemical inertness, and dielectric properties. In particular, their absorption/emission properties in the mid‐infrared range render them suitable structures for ambient temperature thermal emitters. However, the synthesis of uniform, spherical structures is still challenging. Here, we present a robust synthesis procedure based on carbothermal reduction of silica precursor particles. With an isotropic shrinkage of ∼30 %, the spherical particle shape and uniformity are retained. Furthermore, we outline the influence of the gas atmosphere during the carbothermal treatment and demonstrate the successful conversion to SiC by electron microscopy, X‐ray diffraction, thermal and optical analysis. Abstract :